EDUKASI DAN PRAKTIK GOSOK GIGI UNTUK ANAK USIA PRASEKOLAH DI TK NIDZAMYAH KOTA KEDIRI - Wulandari, Siswi; Rofiah, Khofidhotur; Ardela, Mayasari Putri; Fitriasnani, Meirna Eka; Nikmah, Anis Nikmatul (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service activity was carried out on Thursday, 18 July 2025, at TK Nidzamyah, Campurejo Subdistrict, Mojoroto District, Kediri City. The participants were 53 preschool children, 6 teachers, and 40 parents/guardians. The activity aimed to improve children’s knowledge and skills in brushing their teeth correctly and to cultivate clean and healthy living habits from an early age. The program began with an interactive education session using visual media, storytelling, songs, and a dental phantom puppet to explain the importance of brushing teeth twice a day. This was followed by a demonstration of the six correct tooth-brushing steps, accompanied by hands-on practice by the children. Teachers and parents also took part in a brief educational session to support the continuation of tooth-brushing habits at home and at school. The results showed a significant increase in children’s understanding and skills, as well as a joint commitment between the school and parents to continue the tooth-brushing routine. Educational media such as posters, songs, and activity guides were distributed to support ongoing learning. This program is expected to serve as an educational model that can be replicated in other early childhood education institutions in Kediri City.